PENGARUH KONSENTRASI ETANOL TERHADAP TOTAL FENOLIK DAN FLAVONOID SERTA AKTIVITAS ANTIOKSIDAN DARI DAUN KUNYIT (Curcuma longa L.) DENGAN METODE ABTS - Nurcahyani, Dona Agustin; Raharjo, Danang; Apriliawan, Hidayah (Jurnal Buana Farma, 2025)
Turmeric's leaves possess the greatest antioxidant potential. Therefore, further utilization of flavonoid and phenolic compounds is necessary as antioxidants and to enhance their bioactivity as a medicine. This study aimed to determine the effect of ethanol concentration on total phenolic content using the Folin-Ciocalteau analysis method while total flavonoid content using the AlCl₃ analysis method and antioxidant activity of turmeric leaves using the ABTS method, The research design used was experimental research. The results obtained were ethanol concentrations of 50%, 70% and 96%, The results showed that 70% ethanol extract had the highest phenolic content with an average of (63.77 ± 0.40 mg GAE / g), and 70% ethanol extract had the highest flavonoid content with an average of (22.88 ± 0.5 mg QE / g). However, the strongest antioxidant activity was shown by 96% ethanol extract with an IC₅₀ value of (46.36 ± 1.15 ppm (<50 ppm). Thus, turmeric leaf extract with 96% ethanol solvent had the strongest antioxidant activity, while 70% ethanol produced the highest phenolic and flavonoid levels.